An integrated approach for evaluating lean innovation practices in the pharmaceutical supply chain - Ieva Meidute-Kavaliauskiene; Halil Ibrahim Cebeci; Shahryar Ghorbani; Renata Činčikaitė (Logistics, 2021)
Backgroung: Lean innovation focuses on minimizing waste in the product development stages in order to increase productivity by obtaining customer feedback more quickly and efficiently. The usage of lean innovation practices in product development stages in the pharmaceutical supply chain is the topic of an increasing amount of research on the critical question of how lean innovation practices can be implemented in a pharmaceutical supply chain or logistic sector. To answer this question, we first identified lean innovation practices by reviewing the literature. Methods: the identified practices were screened using the fuzzy Delphi method (FDM). The expert panel included eight persons working in pharmaceutical supply chain fields. In the next step, the causal relationships between practices were analyzed using the Gray DEMATEL (GDEMATEL) technique. Results: show that technological knowledge was the most crucial factor in lean innovation practices in the pharmaceutical supply chain. Conclusions: Actualizing lean innovation in the supply chain is more than just utilizing the correct strategies and instruments. To execute lean innovation effectively, a reevaluation must be accomplished: A culture that recognizes requirements for change and is set up for consistent change is essential. Methodological strategies such as the value system cannot be set up as a one-time strategy. To execute lean innovation on a long-haul premise, members must be included and become acclimated to a proceeding with the progress process. Changes in forms are frequently used because of an absence of association of suppliers, regardless of whether measures are sensible.
Keywords: 650; gray DEMATEL; lean innovation; lean innovation practice; prototyping